Madame Blueberry a lesson in thankfulness - Burns, Megan Moore; Vischer, Phil.; Nawrocki, Michael; Olsen, Chris; Big Idea Productions; Warner Home Video (Firm) ([Lombard, Ill.] : Big Idea Productions ; Burbank, CA : Distributed by Warner Home Video, 2003)
A greedy blueberry learns to appreciate what God has given every growing thing.
DVD; Dolby digital 5.1 surround or 2.0 stereo.; region 1.
DVD-ROM system requirements not listed.
Computer animation.
Title and subtitle from container.
Voices: Megan Moore Burns, Phil Vischer, Mike Nawrocki.
Animation director, Thomas Danen ; score, Kurt Heinecke.
Keywords: Avarice -- Juvenile films; Gratitude -- Juvenile films; Virtues -- Juvenile films; Christian life -- Juvenile films; Video recordings for hard of hearing people; Gratitude; DVD-Video discs; Children's films; Computer animation